PWE-412 Oral analgesia for post-operative colorectal patients. (22nd June 2015) - Buchan, S; Williams, L; Bamford, R; Wood, A; Mackey, P
Abstract : Introduction: The WHO analgesic ladder is a well-recognised tool for managing post-operative pain. The aim of this prospective study was to identify if patients undergoing elective colorectal surgery were both prescribed and receiving adequate and appropriate oral analgesia. Method: All patients who underwent elective colorectal surgery over a 4 week period were included. Regular and as required oral analgesia prescribed and administered on day 1, 3 and 5 post-op were recorded. The pain score at these time intervals and the use of any additional local anaesthetic were also recorded. Results: 17 patients met the criteria for inclusion. 4 patients had rectus sheath catheters placed, 3 had patient-controlled analgesia and 5 had a "one shot" spinal bolus. Day 1 post-op all patients were prescribed regular paracetamol and 53% received this. Additional analgesia was required in 58% of patients, half of whom did not receive their regular oral analgesia and 8 were prescribed only paracetamol regularly. 24% of all patients on day 1 post-op had a pain score ≥1. On day 3 post-op all patients were prescribed regular paracetamol and 50% received this. Of those who required supplementary analgesia on day 3, only paracetamol was given regularly. 13% of all patients on day 5 post-op had a pain score ≥1. Half of patients on day 5 post-op did not receive their regularly prescribed paracetamol. Of these patients, 2 required addition analgesia. All patients had a pain score of 0 on day 5. Conclusion: At day 1 and 3 post-colorectal surgery not all patients received adequate analgesia despite oral analgesia being prescribed, although at day 5 all patients were pain free. It is apparent that the WHO analgesic ladder is not being adhered to for management of pain post-colorectal surgery. Disclosure of interest: None Declared.